2016
DOI: 10.1089/ped.2016.0675
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in Schools: Results of the EPIPEN4SCHOOLS Survey Combined Analysis

Abstract: A pilot survey described the characteristics of anaphylactic events occurring in an initial set of participating U.S. schools during the 2013–2014 school year. This survey was subsequently readministered to large school districts, which were underrepresented in initial results. A cross-sectional survey was administered to the U.S. schools that were participating in the EPIPEN4SCHOOLS® program (Mylan Specialty L.P., Canonsburg, PA) to assess characteristics of anaphylactic events. Data from large school distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Other studies included education for school nurses about food allergies (Chokshi, Patel, & Davis, 2015), adolescent relationship abuse and how to integrate discussions of healthy/unhealthy relationships in each student encounter (Raible et al, 2017), school preparedness for biological events (Rebmann, Elliott, Artman, VanNatta, & Wakefield, 2016), how to support students as they return to the classroom (i.e., return to learn) after concussions (Wing, Amanullah, Jacobs, Clark, & Merritt, 2015), recognizing children at risk for maltreatment (Jordan, MacKay, & Woods, 2017), and improving communication with families on weight-related health issues through a web-based tutorial (Steele, Wu, Cushing, & Jensen, 2013). School nurses also assisted with creating an education module about food allergies for school staff (White et al, 2016) and provided recommendations for education on collaboration with interdisciplinary staff as well as conducting mandated screenings to provide care for students with disabilities (Singer, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies included education for school nurses about food allergies (Chokshi, Patel, & Davis, 2015), adolescent relationship abuse and how to integrate discussions of healthy/unhealthy relationships in each student encounter (Raible et al, 2017), school preparedness for biological events (Rebmann, Elliott, Artman, VanNatta, & Wakefield, 2016), how to support students as they return to the classroom (i.e., return to learn) after concussions (Wing, Amanullah, Jacobs, Clark, & Merritt, 2015), recognizing children at risk for maltreatment (Jordan, MacKay, & Woods, 2017), and improving communication with families on weight-related health issues through a web-based tutorial (Steele, Wu, Cushing, & Jensen, 2013). School nurses also assisted with creating an education module about food allergies for school staff (White et al, 2016) and provided recommendations for education on collaboration with interdisciplinary staff as well as conducting mandated screenings to provide care for students with disabilities (Singer, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies in various countries have examined potential strategies for schools to address the risks of food allergies, such as becoming ‘peanut‐free’ and making adrenaline available to school staff, with some controversy 115,116,119–127 . A survey of school nurses in Massachusetts found that 10.3% of schools do not permit peanuts to be sent in from home, 91.1% had peanut‐free tables, and 65.6% had peanut‐free classrooms 128 .…”
Section: The Burden Of Peanut Allergy On the Individualmentioning
confidence: 99%
“…In the United States (US), 115 anaphylaxis reactions requiring adrenaline at school (2001)(2002)(2003) have been reported, and the Epipen4schools ® program provided data on allergic reactions that occurred in the 6574 responding schools (2013-2014). 4,5 In France, prevention measures to improve the acceptance of children with allergic disease and reduce the risk of anaphylaxis at school through individual healthcare plans (IHP) were introduced into law in 2003.…”
Section: Gaps In the Management Of Food-induced Anaphylaxis Reactionsmentioning
confidence: 99%